Program Promotif Dan Preventif Dalam Upaya Pencegahan Infeksi Saluran Pernapasan Akut (ISPA) - Safidni, Elvira; Sutriyati, Sutriyati; Rosdiana, Rosdiana; Jumadil, Hamdani; Pannyiwi, Rahmat (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2026)
Acute Respiratory Tract Infections (ARI) are one of the most common public health problems and a major cause of morbidity, especially in children, the elderly, and vulnerable groups. The high incidence of ARI is closely related to behavioral factors, environmental conditions, and low public knowledge about disease prevention. Promotive and preventive programs are a strategic approach to reducing the incidence of ARI by increasing knowledge, awareness, and changing community behavior. This Community Service activity aims to improve community understanding and practice of ARI prevention through health education and community empowerment. Implementation methods include health education, interactive discussions, demonstrations of clean and healthy living behaviors (PHBS), and evaluation through pre- and post-tests. The results of the activity indicate an increase in community knowledge and attitudes toward ARI prevention. This program is expected to contribute to reducing the risk of ARI and improving public health.